(3YfbGA eZQH aj eYQaI NJe GdChdjGA hTeS GdeZQHs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eUWai Hf YHO GdhgGH Hf SYjO GdUdGMi GdUGdMi s)
(3ChdgG (B:s
(3bGd GdTjN GdhYGA GdeNJhe Ydi GdSQ GdecJhe CeG HYO MeOkG ddg GdPi JbOe cfGbO CdafG cJGHkG QhMGfjkG hEfTGA QHGfjkG SejfGg HGdJOHjQGJ GdCdgjI ai EUdGM GdeedcI GdEfSGfjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1173s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs